Number 16 (November 1986) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1984)
Biology and Conservation of the Slackwater Darter, Etheostoma boschungi (Pisces: Percidae). By H.T. Boschung and D. Nieland, 4 pp. Fishes of the North Fork Holston River System, Virginia and Tennessee. By J.C. Feeman, 7 pp. Fishes of the North Fork Holston River System, Virginia and Tennessee. By J.C. Feeman, 7 pp. Reintroduction of an Undescribed Species of Elassoma into Pryor Branch, Limestone County, Alabama. By M.F. Mettee and J.J. Pulliam, 2 pp., plus News Notes.
Keywords: slackwater darter; etheostoma boschungi; pisces; percidae; north fork holstom river system; virgina; tennessee; buttahatchee; river; alabama; mississippi; elassoma; pryor branch; limestone county